Efficient synthesis of optically active neolignans ligraminol D and E - Ghotekar, Ganesh S.; Mujahid, M.; Muthukrishnan, M. (Synthesis-Stuttgart, 2019)
Efficient syntheses of optically active neolignans ligraminol D and E were achieved in four simple steps starting from easily available chiral benzyl glycidyl ethers. The products were obtained in good overall yields and high enantioselectivities. The protocol might also be useful in the synthesis of other ligraminols or related neolignans.
Keywords: benzyl glycidyl ether; Epoxide; lignan; ligraminol; Mitsunobu